Characterizing early stage sub-micron particle formation during pulverized coal combustion in a flat flame burner. (15th December 2019) - Khatri, Dishant; Gopan, Akshay; Yang, Zhiwei; Adeosun, Adewale; Axelbaum, Richard L.
Graphical abstract: Abstract: Mineral matter evolution, soot formation, and soot oxidation are the governing processes for fine particle evolution during the early stages of pulverized coal combustion. Soot and ash can be simultaneously present in PM 0.1, and experimental results obtained to understand early stage particle formation can be ambiguous if the two are not independently evaluated. A sampling system proposed in this work differentiates between soot and mineral matter by employing a high temperature furnace downstream of the sampling system, supplied with sufficient oxygen to oxidize the soot in the sampled aerosol stream. The stream can be routed either through the furnace or bypassing it. In the bypass configuration, the SMPS measures the total PM size distribution. In the flow-through configuration, the SMPS measures the ash PM size distribution, and the difference identifies the contributions from the soot aerosols. This study has shown that there is a high probability of confounding effects in experimental measurements of early stage ultra-fine particulate matter evolution, and the effects were shown to exist at different conditions and with different coals. The results show that for PRB coal combustion, as residence time increases from 9 ms to 33 ms, the volume of total PM 0.1 decreases by 68%, and the ash PM 0.1 increases by 600%, whereas for Hongshayuan lignite coal, the volume of total PM 0.1 increases by 275%, and ash PM 0.1 increases by 939%. These results indicated that soot constitutes a major part of PM 0.1 during the early stages of fine particle evolution.